2014
DOI: 10.1177/1468087413492962
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-fuzzy model tree approach to virtual sensing of transient diesel soot and NOx emissions

Abstract: Diesel engine combustion and emission formation are highly nonlinear and thus create a challenge related to engine diagnostics and engine control with emission feedback. This article describes the development of neuro-fuzzy models for prediction of transient NOX and soot emission from a diesel engine. The modeling techniques are motivated by the idea of divide and conquer the input–output space. The complex problem is divided into multiple simpler subproblems, which are then identified using simpler class of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…In parallel, Kirchen et al [12] developed a mean value model for soot and showed the effectiveness with tip-in operations employing empirical correlations between engine-out emissions and engine operating conditions. Furthermore, artificial neural networks have been employed by various researchers (e.g., [13,14]) to determine transient emissions based on steady-state test results used to generate the training data. On the other hand, a different prediction approach was followed by Bishop et al [15], who, based on data collected from on-board diagnostics (OBD) and portable emissions measurement systems (PEMS) when driving under real-world conditions, created fuel consumption and emission engine maps of real-world driving.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, Kirchen et al [12] developed a mean value model for soot and showed the effectiveness with tip-in operations employing empirical correlations between engine-out emissions and engine operating conditions. Furthermore, artificial neural networks have been employed by various researchers (e.g., [13,14]) to determine transient emissions based on steady-state test results used to generate the training data. On the other hand, a different prediction approach was followed by Bishop et al [15], who, based on data collected from on-board diagnostics (OBD) and portable emissions measurement systems (PEMS) when driving under real-world conditions, created fuel consumption and emission engine maps of real-world driving.…”
Section: Introductionmentioning
confidence: 99%
“…As was the case with other similar mappingbased approaches developed in the past [10][11][12][13][14][18][19][20][21][22][23], the context of quasi-linear modeling [24] is, in general, followed.…”
Section: Methodology-engine and Vehicle Modelmentioning
confidence: 99%
“…The soot emission values at points within a free of data space in the torque–speed map are interpolated by various mathematical models including the local linear regression and the neuro-fuzzy models. 27,28 Under a transient engine operating condition, the soot emission predicted from the map for a steady-state condition has to be modified, so that the spiky higher soot emission due to a short-term oxygen deficit could be taken into account.…”
Section: Cumulative Soot Sensormentioning
confidence: 99%